KEMANDULAN REZIM ORGANISASI KERJASAMA ISLAM DALAM PERLINDUNGAN TERHADAP AL-AQSA - Arif, Muhammad Qobidl ‘Ainul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
The Fourth Summit of the Organization of Islamic Cooperation (OIC) at 1984 in Casablanca Morocco had issued Resolution 2/4-P(IS) which puts attention to the City of al-Quds. The resolution condemned Israeli government who destroyed religious sites in al-Aqsa Mosque complex, asked for reversion of the Palestinian sovereignty over al-Aqsa Mosque, and commanded the OIC members to make all necessary actions to impose sanctions against Israeli government politi¬cally, economically and culturally. Ineffectiveness of this resolu¬tion has been mainly caused by a number of factors, are: firstly, the level of colla¬¬bo¬ra¬tion and collectivity among the members of the OIC is low. Secondly, the resolution is highly vulnerable.Thirdly, there is no such rule in the OIC which ensures the implementation of the OIC’s resolu¬tions for its members.There is no a dominant state which becomes the leader of the OIC. This condition has been worsened by the lack of epistemic community roles in the drafting process of the OIC resolutions